Meningkatkan Kualitas Pendidikan melalui Penggunaan Bahasa yang Efektif di Perguruan Tinggi - Hasanah, Uswatun (STKIP PGRI Bandar Lampung, 2025)
Effective language use in higher education plays an important role in improving the quality of education, because language is not only a communication tool, but also a key instrument in learning. This study aims to examine how clear and communicative language use can affect understanding of teaching materials and classroom interaction. Using a qualitative approach with a case study method, this study involved lecturers and students at two universities in Indonesia. Data were collected through in-depth interviews and classroom observations. The results show that the use of simple, clear, and jargon-free language can improve students' understanding of the material, strengthen interactions between lecturers and students, and encourage active student participation in class discussions. However, the use of foreign languages, especially English, as the language of instruction in some courses poses challenges, especially for students with limited proficiency in those languages. This study suggests that universities provide language training for lecturers and students and simplify the academic language used in teaching to optimize the learning process. These findings are in line with previous studies that state that clear communication contributes to improving the quality of teaching.